Development of polycarbonate-containing block copolymers for thin film self-assembly applications. Issue 4 (16th December 2015) - Vora, Ankit; Wojtecki, Rudy J.; Schmidt, Kristin; Chunder, Anindarupa; Cheng, Joy Y.; Nelson, Alshakim; Sanders, Daniel P.
Abstract : High quality block copolymers are needed for thin film self-assembly and directed self-assembly applications. Abstract : Access to well-defined materials is one of the key requirements for successful implementation of block copolymer-based lithography for advanced semiconductor nodes. We report on the development of polystyrene- b -polytrimethylene carbonate (PS- b -PTMC) block copolymer (BCP) using organocatalytic ring opening polymerization of trimethylene carbonate (TMC) from hydroxyl-functional polystyrene macroinitiator as a materials candidate for directed self-assembly applications. The impact of organocatalyst choice and the extent of TMC conversion on the quality of PS- b -PTMC BCP were studied using gel permeation chromatography and nuclear magnetic resonance (NMR) spectroscopy techniques. As a direct method to identify PTMC homopolymer content in the resulting BCPs, a new NMR-based technique was developed. Finally, the influence of BCP purity on the thin film morphology was studied using atomic force microscopy and grazing incidence small angle X-ray scattering techniques. Our results indicate that the PTMC homopolymer impurity negatively impacts the thin film morphology, which is extremely important for lithographic applications.